Optimalisasi Strategi Agribisnis Pangan Lokal di Wamena: Pendekatan Analytical Hierarchy Process (AHP) - Berliana, Meri; Inrianti, Inrianti; Sihombing, Sari Dame Arta Suryani; Pumoko, Patras (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Local food agribusiness in Wamena holds significant potential but still faces various fundamental challenges in its development. This study aims to examine the potential, constraints, and perspectives of local farmers regarding the development of local food-based agribusiness in Wamena, Papua Highlands. A structured survey was conducted with 10 farmers to explore current conditions and the strategies needed. The Analytical Hierarchy Process (AHP) method was applied to objectively determine strategic priorities for agribusiness development through pairwise comparisons and consistency tests. The findings indicate that commodities such as sweet potatoes, taro, and cassava have high market potential; however, their development is hindered by limited capital, restricted access to modern agricultural technology, inadequate transportation and storage infrastructure, and insufficient distribution networks. The AHP analysis identified three main priorities: integrating local wisdom with innovation, strengthening the role of local government and customary institutions, and reinforcing farmer organizations accompanied by digital marketing assistance. These findings highlight the importance of collaboration between local cultural practices and technological innovation to build a sustainable agribusiness system. Government policy support, infrastructure development, and digital-based training are key factors in enhancing the competitiveness of Wamena’s local food products. Thus, this study provides strategic recommendations for government, customary institutions, and other stakeholders to foster the development of inclusive, adaptive, and competitive local food agribusiness in broader markets.